First to 15: Alberta's minimum wage policy on employment by wages, ages, and places - Sebastian Fossati; Joseph T. Marchand (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
Most minimum wage studies are identified on small, plentiful, and expected wage changes, spread out over time. A recent set of changes have instead been large, unexpected, and quick, following the "Fight for 15" movement. Alberta is the first state or province to have this 15 minimum wage, with an unexpectedly large increase (47%) occurring over a short horizon (3 years). The employment effects of this policy are estimated using a synthetic control approach on Labour Force Survey data. Similar to the existing literature, workers moved up the wage distribution, increment by increment, reaching past the 15th percentile, but not all remained employed. Employment losses were found mostly among younger workers, at magnitudes similar to previous elasticities. Newer to the literature, regional employment losses were found mostly outside of Alberta's two main cities, but youth employment losses were similar between urban and non-urban areas, with an urban older worker offset.
Keywords: J21; J38; J48; J82; R23; 330; employment; Fight for 15; geography; minimum wage; synthetic control